Deciphering late Devonian–early Carboniferous P–T–t path of mylonitized garnet-mica schists from Prins Karls Forland, Svalbard - Kośmińska, Karolina; Spear, Frank S.; Majka, Jarosław; Faehnrich, Karol; Manecki, Maciej; Piepjohn, Karsten; Dallmann, Winfried (Journal of Metamorphic Geology, 2020)
This is the peer reviewed version of the following article: Kośmińska, K., Spear, F. S., Majka, J., Faehnrich, K., Manecki, M., Piepjohn, K. & Dallmann, W. K. (2020). Deciphering late Devonian–early Carboniferous P–T–t path of mylonitized garnet-mica schists from Prins Karls Forland, Svalbard. Journal of Metamorphic Geology, ? (?), ?., which has been published in final form at https://doi.org/10.1111/jmg.12529 . This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Use of Self-Archived Versions. Quartz‐in‐garnet inclusion barometry integrated with trace element thermometry and calculated phase relations is applied to mylonitized schists of the Pinkie unit cropping out on the island of Prins Karls Forland, western part of the Svalbard Archipelago. This approach combines conventional and novel techniques and allows deciphering of the pressure–temperature ( P–T ) evolution of mylonitic rocks, for which the P–T conditions could not have been easily deciphered using traditional methods. The results obtained suggest that rocks of the Pinkie unit were metamorphosed under amphibolite facies conditions at 8–10 kbar and 560–630°C and mylonitized at ~500 to 550°C and 9–11 kbar. The P–T results are coupled with in‐situ Th–U‐total Pb monazite dating, which records amphibolite facies metamorphism at c. 359–355 Ma. This is the very first evidence of late Devonian–early Carboniferous metamorphism in Svalbard and it implies that the Ellesmerian Orogeny on Svalbard was associated with metamorphism up to amphibolite facies conditions. Thus, it can be concluded that the Ellesmerian collision between the Franklinian margin of Laurentia and Pearya and Svalbard caused not only commonly accepted brittle deformation and weak greenschist facies metamorphism, but also a burial and deformation of rock complexes at much greater depths at elevated temperatures.